Osadnictwo pradziejowe na terenie wsi Ochla l jej najbliższych okolic = Ancient settlements on the territory of present-day Ochla and its neighbourhood - Bobowski, Bogdan; Towpik, Paweł Szymon (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The over-700-years-long history of the village of Ochla sort of obliges one to conduct a thorough research on its origins. A study of ancient settlements would allow oneto compile a considerably complete catalogue of ancient archaeological sites. This paper is based on a body of archaeological data scattered in various, difficult-to-find German and Polish scientific periodicals. This collection of data along with conclusions and suggestions for further research will certainly be a good starting point for the development of a monograph of Ochla's history from the Stone Age to modern times.
Keywords: Ochla (lubuskie) - historia; osadnictwo - Polska; archeologia